Above the Birch Line : Poems - Taavila, Pia (Book collections on Project MUSE., 2021)
"This poetry collection is mainly autobiographical; we are led through the author's recounting of childhood, travels, motherhood, and finding love. There are also poems that explore the themes of aging and death"--